The Role of Visual Representation for High School Physics in Teaching of Classical Mechanics - Godelfridus Hadung Lamanepa; Claudia M.M Maing; Maria Ursula Jawa Mukin; Alfons Bunga Naen (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This study aims to highlight the importance of visual representation skills in classroom practice, especially in classical mechanics physics, by discussing (1) free-body diagram representation, (2) resultant force system, (3) types and directions of quantities, (4) representation of results and units. This research was conducted on 30 students in second grade at Beringin Kupang High School. The research method was carried out experimentally using a special image representation test tool for classical mechanical materials. The research data were analyzed by descriptive method. The results showed that (1) more than 50% of students did not draw FBD before solving the problem, (2) the success rate of students in representing the resultant force system was the highest at 33%, (3) determining the type and direction of motion the success rate was 67%, and (4) representation results and units with a success rate of 40%. The results of this study become a reference for increasing the role of visual representation in learning physics.